A Review: Contact Electrification on Special Interfaces - Zhang, Wenhao; Shi, Yuxiang; Li, Yufang; Chen, Xiangyu; Shen, Honglie (Frontiers in Materials, 2022)
The contact electrification of materials plays an important role in developing and applying triboelectric nanogenerators (TENGs). By exploring the contact electrification phenomena at different interfaces, we can improve the understanding of the electrification mechanism and expand the application field of TENGs. In this way, the rate of energy utilization can be improved while the harm caused by the electrostatic effect is reduced. This paper systematically summarized the different interfaces contact between the research status quo of electricity, this paper expounds the solid-solid, liquid-solid interface, and liquid-liquid interface, as well as the gas and other interface contact electrification mechanism, and the research and application of them, are introduced, finally prospects the occurred in the contact between the different interface of electric potential applications as well as the challenge.